Traditional Sporting Games as Emotional Communities: The Case of Alcover and Moll’s Catalan–Valencian–Balearic Dictionary - Costes, Antoni; March-Llanes, Jaume; Muñoz-Arroyave, Verónica; Damian-Silva, Sabrine; Luchoro-Parrilla, Rafael; Salas-Santandreu, Cristòfol; Pic, Miguel; Lavega-Burgués, Pere (Frontiers in Psychology, 2021)
Learning to live together is the central concern of education everywhere in the world (UNESCO). Traditional sporting games (TSGs) provide interpersonal experiences that shape miniature communities charged with emotional meanings. This study analysed the ethnomotor features of TSG (relationship between the internal characteristics of the TSG and socio-cultural variables) in three Catalan-speaking Autonomous Communities and interprete them for constructing emotional communities. Methodology. Sample. We studied 503 games collected in the dictionary català-valencià-balear de Alcover and Moll (1926-1963). Instruments and procedure. A database was built up with the information about the internal and external logic of TSG. The validity of the information was confirmed by means of a concordance test between the researchers. Data analysis. Data processing was carried out using contingency tables (descriptive level) and classification trees (inferential level), identifying the predictive variables of the types of TSG. Results. Most of the TSG were sociomotor games (n = 405/503; 80.5%). The classification tree identified four explanatory variables. Three variables were internal traits (body contact, material and score) and one variable corresponded to external logic (age). Discussion: Features of the Catalan TSG build original emotional communities. The ethnomotor regularities triggered emotional experiences associated with pleasure for: a) Living together (predominance of sociomotor games); b) domesticating of aggressiveness over opponents (different motor licit aggressiveness); c) developing sustainability (presence and absence of objects from the surrounding environment); and d) educating the competition (games with and without final score); e) interpersonal well-being based on the community (transmission from children to young TSG)